Banana fibers camouflaging as a gut worm in a 6-month-old infant - Abhinandan Patil (Emergency Department of Hospital San Pedro (Logroño, Spain), 2020)
Worm infestation issue is a common health condition observed mostly in Asian countries. The prevalence of worms in children is higher due to the habit of playing in mud or outdoors which is not found in the case of an infant. Very rarely worm infestation is observed in infants. There is a need for an investigation to be carried out for live worms in the stool. Sometimes the change in the diet of the infant, irregular bowel movements, and worm-like things in stool makes an alarming situation. We report the original case of a 6-month-old infant camouflaging for worm infestation due to the presence of the thread-like parasite in stool. The routine stool and chemical analysis of black thread thing from stool revealed solid diet fibers of banana and not any parasitic infection.